2018
DOI: 10.1590/fst.09517
|View full text |Cite
|
Sign up to set email alerts
|

Optimized conditions to produce water-in-oil-in-water nanoemulsion and spray-dried nanocapsule of red ginseng extract

Abstract: The aim of this study was to optimize conditions for producing water-in-oil-in-water (W/D/W) nanoemulsion and spray-dried nanocapsule of red ginseng extract. Based on emulsion stability and average particle size analysis, optimum conditions to produce W/D/W nanoemulsion were: ratio of core to coating material, 3:7; primary emulsifier, 10% polyglycerol polyricinoleate; ratio of W/D phase to coating material, 1.5:8.5; secondary emulsifier, 10% polyoxyethylene sorbitan monolaurate; solvent, 20% ethyl acetate; sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 31 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…The drop size distribution of the flavorings is in good agreement with, 41 where MD, WPC, and GA were used to encapsulate red ginseng extract with particle sizes ranging from 100 nm to 3 μm. Also, nano-encapsulated M. piperita using chitosan and Alyssum homolocarpum gum with a particle size distribution range from 490–790 nm demonstrated that the droplet size distribution is consistent across all samples.…”
Section: Resultssupporting
confidence: 73%
“…The drop size distribution of the flavorings is in good agreement with, 41 where MD, WPC, and GA were used to encapsulate red ginseng extract with particle sizes ranging from 100 nm to 3 μm. Also, nano-encapsulated M. piperita using chitosan and Alyssum homolocarpum gum with a particle size distribution range from 490–790 nm demonstrated that the droplet size distribution is consistent across all samples.…”
Section: Resultssupporting
confidence: 73%
“…According to Gharibzahedi et al (2012), RSM is a collection of useful mathematical and statistical procedures, and it needed to scrutinize multiple factors and their interactions in comparison to other approaches for possessing the advantage of reducing number of experimental trials. Min et al (2018) optimized the nanoencapsulation efficiency with different emulsifiers using RSM in red ginseng extract nanoencapsulation. On the study, the increase of emulsifiers led to nanoencapsulation increase.…”
Section: Optimization Of Conditions For Producing Microemulsion Of Tomentioning
confidence: 99%
“…However, no activity was detected against P. aeruginosa PT3087 (MIC > 500 µL/mL). The observed antibacterial activity against sensitive strains could be related to the ability of some lipids to destabilize the phospholipid membrane of bacterial cells [ 52 ].…”
Section: Resultsmentioning
confidence: 99%